Characteristics of Forest and Manuka Honey As Well As Their Application As Herbal Honey Drinks With The Addition of Qusthul Hindi and Turmeric - Aulia Septiani; Tuti Suryati; Astari Apriantini; Yuni Cahya Endrawati (Faculty of Animal Science Universitas Brawijaya, 2022)
Manuka and forest honeys are types of honeys that are widely consumed because for their antioxidant properties. In this study, the properties of forets and manuka honey and the use of honey as a herbal drink with the addition of Qusthul hindi and turmeric were analyzed. The addition of Qusthul hindi (0,125 g and 0,375 g) and turmeric (0,125 g and 0,375 g) is given in two formulations. This study was conducted in two phase, namely analyzing the characteristics of manuka and forest honey and preparing herbal drinks to then analyzing their properties. The results showed that the properties of forest honey do not meet the standards for the variables of pH, HMF value, and diastase enzyme activity, while Manuka honey meets the standards only for variables of moisture, HMF value, and diastase enzyme activity. The addition of Qusthul hindi and turmeric to herbal drinks results in an increase in pH, DPPH inhibitoty activity, and antioxidant capacity, as well as a decrease of water content, but is not sensory evaluated because the addition of spices causes changes in taste and appearance.